Association between executive functions and gross motor skills in overweight/obese and eutrophic preschoolers: cross-sectional study - Fernandes, Amanda Cristina; Viegas, Ângela Alves; Lacerda, Ana Cristina Rodrigues; Nobre, Juliana Nogueira Pontes; Morais, Rosane Luzia De Souza; Figueiredo, Pedro Henrique Scheidt; Costa, Henrique Silveira; Camargos, Ana Cristina Resende; Ferreira, Fernanda De Oliveira; de Freitas, Patrícia Martins; Santos, Thiago; da Silva Júnior, Fidelis Antônio; et al. (BMC Pediatrics, 2022)
Preschool age (3–5 years old) is a crucial period for children to acquire gross motor skills and develop executive functions (EFs). However, the association between the qualitative gross motor skills and EFs remains unknown in preschoolers, especially among overweight and obese children.
Keywords: Child development; Childhood obesity; Cognitive flexibility; Cognitive function; Executive functions; Gross motor; Object control; Planning; Tower of Hanoi; Verbal fluency